Pengaruh Putaran Screw terhadap Keluarnya Adonan dari Nosel Mesin Pencetak Bakso - Bambang Sugiyanto; Burhan Ibnu Mubtadi (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Politeknik Pratama Mulia Surakarta, 2018)
The process of making meatballs is generally done using meatball moulding machine and machine owned by the manufacturer can only produce one type of meatball size. While consumers (culinary lovers of meatballs) there who want a sphere of meatballs that are smaller or larger or even form a long cylinder meatball like sausage. To design a meatball moulding machine that can produce meatballs with a variety of shapes and sizes the first thing to know is the speed of the meatball dough out of the nozzle mouth due rotation of screw in the mouthpiece dough. This study examines the relationship between rotation screw meatball moulding machine to the speed of the dough out of the machine nozzle mouth. The research method is done by varying the rotation of the screw axis and measuring the dough velocity out of the nozzle of the moulding machine. Data analysis was performed to obtain mathematical equations of the relationship between rotation screw meatball moulding machine to the speed of the dough out. The results showed that the higher the rotation the greater the dough velocity out of the dough funnel nozzle, but not directly proportional. Mathematical equations are very useful as a reference for the designer meatball machine designers if designing machines with a variety of shapes and sizes of meatballs.